2020
DOI: 10.1029/2019gb006520
|View full text |Cite
|
Sign up to set email alerts
|

Improving a Biogeochemical Model to Simulate Surface Energy, Greenhouse Gas Fluxes, and Radiative Forcing for Different Land Use Types in Northeastern United States

Abstract: Land use changes exert important impacts on climate, primarily through altering greenhouse gas (GHG) and surface energy fluxes. Biogeochemical models have incorporated a relatively complete suite of biogeochemical processes to simulate GHG fluxes. However, these models often lack detailed processes of surface energy exchange, limiting their ability to assess the impacts of land use change on climate. In this study, we incorporated processes of surface energy exchange into a widely used biogeochemistry model, D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…According to Khan, [48], tillage, which is the standout feature of the 2019 (evaluation) period, can stimulate soil microbial activity and thus respiration. Nevertheless, simulated NEE was not significantly different from observed (-14%), in line with the findings of Deng et al ., [41] who also reported a good match for NEE, and of Abdalla et al, [26] who reported a corelation of R = 0.6 for NEE simulations compared to measured data on permanent grassland in the Republic of Ireland.…”
Section: Ghg Exchangementioning
confidence: 77%
See 2 more Smart Citations
“…According to Khan, [48], tillage, which is the standout feature of the 2019 (evaluation) period, can stimulate soil microbial activity and thus respiration. Nevertheless, simulated NEE was not significantly different from observed (-14%), in line with the findings of Deng et al ., [41] who also reported a good match for NEE, and of Abdalla et al, [26] who reported a corelation of R = 0.6 for NEE simulations compared to measured data on permanent grassland in the Republic of Ireland.…”
Section: Ghg Exchangementioning
confidence: 77%
“…The nitrification, denitrification, and fermentation sub-models simulate C and N transformations that are mediated by soil microbes and controlled by soil environmental factors and concentrations of relevant substrates [39], [40]. The DNDC model adopted in this study was further improved to simulate surface energy exchange, soil frost and thaw dynamics, and C gas fluxes in cold regions [41]- [43].…”
Section: The Dndc Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The DNDC model (Li et al., 1992a , 1992b ) used in this study was originally developed for quantifying carbon (C) sequestration and GHG emissions from agroecosystems, and has been extensively applied to simulate N 2 O emissions from different types of ecosystems (Deng et al., 2020 ; Gilhespy et al., 2014 ; Giltrap et al., 2010 ). The model simulates soil C and N transformations through a series of biogeochemical reactions, such as decomposition, microbial assimilation, plant uptake, ammonium adsorption, ammonia volatilization, nitrification, denitrification, and nitrate leaching.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, there are large uncertainties regarding their behaviors in modeling SOC changes and CO 2 fluxes due to very limited model testing against field-scale observations. The process-based biogeochemical model, DNDC, has incorporated a relatively complete suite of biophysical and biogeochemical processes and FMPs, which enables it to simulate vegetation growth, transport and transformations of C and nitrogen (N), SOC changes, and greenhouse gas (GHG) fluxes in terrestrial ecosystems (e.g., Deng et al, 2018Deng et al, , 2020Gilhespy et al, 2014;Giltrap et al, 2010;Li, 2000;Li et al, 1992aLi et al, , 2012. However, DNDC does not explicitly simulate microbial or enzymatic decomposition of SOM, and therefore is unable to reproduce microbial regulations on soil C cycle.…”
Section: Introductionmentioning
confidence: 99%